Behavior Composition as Fully Observable Non-Deterministic Planning - Ramirez, Miquel; Yadav, Nitin; Sardina, Sebastian (Proceedings of the International Conference on Automated Planning and Scheduling, 2013)
The behavior composition problem involves the automatic synthesis of a controller able to “realize” (i.e., implement) a target behavior module by suitably coordinating a collection of partially controllable available behaviors. In this paper, we show that the existence of a composition solution amounts to finding a strong cyclic plan for a special non-deterministic planning problem, thus establishing the formal link between the two synthesis tasks. Importantly, our results support the use of non-deterministic planing systemsfor solving composition problems in an off-the-shelf manner. We then empirically evaluate three state-of-the-art synthesis systems (a domain-independent automated planner and two game solvers based on model checking techniques) on various non-trivial composition instances. Our experiments show that while behavior composition is EXPTIME-complete, the current technology is already able to handle instances of significant complexity. Our work is, as far as we know, the first serious experimental work on behavior composition.